PENINGKATAN LITERASI KEWIRAUSAHAAN MELALUI BUSINESS MODEL CANVAS PADA SISWA SMPK SANG TIMUR, JAKARTA (SULUH: Jurnal Abdimas, 2025)
SMP Katolik Sang Timur Jakarta faces the challenge of low student understanding of entrepreneurship concepts and presentation skills, requiring a practical and participatory learning method. This community service program aims to enhance entrepreneurial literacy and public speaking skills through the introduction of the Business Model Canvas (BMC). The activity was conducted on ninth-grade students. The method was applied through stages of material delivery, group discussions, canvas completion, and presentation of results. Evaluation was carried out using pre-tests and post-tests. The results showed an increase in the average understanding score and accompanied by improved confidence, creativity, and teamwork. The implication of this activity is that BMC can be an effective medium for entrepreneurship learning at the secondary school level and can be replicated in other schools to foster entrepreneurial interest from an early age.